Theoretical Aspects of Distributed Computing in Sensor Networks - Nikoletseas, Sotiris (Monographs in Theoretical Computer Science. An EATCS Series, 2011)
aWireless ad hoc sensor networks has recently become a very active research subject. Achieving efficient, fault-tolerant realizations of very large, highly dynamic, complex, unconventional networks is a real challenge for abstract modelling, algorithmic design and analysis, but a solid foundational and theoretical background seems to be lacking. This book presents high-quality contributions by leading experts worldwide on the key algorithmic and complexity-theoretic aspects of wireless sensor networks. The intended audience includes researchers and graduate students working on sensor networks, and the broader areas of wireless networking and distributed computing, as well as practitioners in the relevant application areas. The book can also serve as a text for advanced courses and seminars.